A point difference analysis established by winners and losers in international badminton doubles matches - Reddy, A.; Bagchi, A.; Madkekar, G. V.; Pratap, B.; Acharya, A.; Mishra, A. (SportMont, 2024)
The aim of this study is to analyze the point difference established in three different phases between winners and losers in international men`s and women`s badminton doubles matches. Analyzing 183 matches from the 2021 TotalEnergies World Championship, each match was divided into three phases: Phase 1 (0-7 points), Phase 2 (8-14 points), and Phase 3 (15-21 points). Maximum Point Difference (MPD) and Maximum Consecutive Points (MCP) were examined to assess player per formance. Kruskal-Wallis H and Mann-Whitney U statistical tests were conducted. Significant differences between win ners and losers were found in all phases, with the difference increasing significantly over phases with medium to large effect sizes. The first seven points significantly increase a player`s chances of winning. 72% (men`s category) and 75% (women`s category) of players won, who was ahead in the point difference in the first phase of the game. In the men`s category, 67.4% won who were ahead in point difference in all three phases. Whereas in the women`s category, it is 70.45%. Winners in both categories had significantly (p<0.05) higher consecutive points than the losers. In the second phase, the winners averaged 5 to 6 points over the losers in both categories. The winners kept increasing their point difference in every phase. On the other hand, in losers, the point difference decreased throughout the game. These findings underscore the importance of early lead acquisition and suggest potential strategies and tactics to enhance players` winning probabilities.